Elements of Facility In Job Satisfaction Of Special Education Teachers In Malaysia - et. al., Ahmad Syarifuddin Che Abd Aziz, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Complete and safe facilities also play an important role in creating satisfaction in carrying out the duties as a special education teacher. Adequate facilities for the learning process can help teachers in avoiding the workload in building their own teaching materials. The situation can make teachers' teaching smoother and able to create job satisfaction. In addition to facility safety, safety when conducting classes and MBK is also a factor to job satisfaction. Job satisfaction is more guaranteed if MBK is not aggressive and provides good cooperation in the classroom. Although basic facilities are not the responsibility of the teacher or school to provide, the importance of obtaining complete facilities is undeniable. Even complete and safe facilities can help students' understanding in a learning. This study was conducted to detail the elements of facilities in creating job satisfaction of special education teachers. This qualitative study uses the interview method as a means of data collection. A total of 11 respondents consisting of special education program coordinators of each district in the state of Johor, Malaysia, were involved in this study. The implications of this study can be used as a reference to stakeholders in providing adequate facilities for special education.